Potential Use of Microbial Electrolysis Cells in Domestic Wastewater Treatment Plants for Energy Recovery - Escapa, Adrián; San-Martín, María Isabel; Morán, Antonio (Frontiers in Energy Research, 2014)
Globally, large amounts of electrical energy are spent every year for domestic wastewater (dWW) treatment. In the future, energy prices are expected to rise as the demand for energy resources increases and fossil fuel reserves become depleted. By using appropriate technologies, the potential chemical energy contained in the organic compounds present in dWWs might help to improve the energy and economic balance of dWW treatment plants. Bioelectrochemical Systems (BESs) in general and microbial electrolysis cells (MECs) in particular represent an emerging technology capable of harvesting part of this energy. This study offers an overview of the potential of using MEC technology in dWW treatment plants (dWWTPs) to reduce the energy bill. It begins with a brief account of the basics of BESs, followed by an examination of how MECs can be integrated in dWW treatment plants (dWWTPs), identifying scaling-up bottlenecks and estimating potential energy savings. A simplified analysis showed that the use of MEC technology may help to reduce up to ~20% the energy consumption in a conventional dWWTP. The study concludes with a discussion of the future perspectives of MEC technology for dWW treatment. The growing rates of municipal water and wastewater treatment markets in Europe offer excellent business prospects and it is expected that the first generation of MECs could be ready within 1-4 years. However, before MEC technology may achieve practical implementation in dWWTPs, it needs not only to overcome important techno-economic challenges, but also to compete with other energy-producing technologies.